FINANCIAL PERFORMANCE ANALYSIS USING ECONOMIC VALUE ADDED (EVA) AND MARKET VALUE ADDED (MVA) METHODS AT PT. DIAGNOSIS LABORATORIUM UTAMA, TBK - Maulana, Izzul Haq Firman (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2024)
The purpose of this study was to determine the company's financial performance using the Economic Value Added (EVA) method and the Market Value Added (MVA) method. Measurement of the company's financial performance is needed to determine success in achieving the goals of a company. The type of research used is descriptive research using a quantitative approach. The object of research is PT Diagnosis Laboratorium Utama (DGNS) Tbk. period 2020 - 2022. The data used is secondary data in the form of financial reports obtained from the Indonesia Stock Exchange (BEI). The data analysis technique uses the EVA and MVA methods. The results of the research conducted show that in 2020 the EVA value is categorized as positive or above 0 (EVA>0). This proves that the company's management has succeeded in creating economic added value for the company and is also able to provide a rate of return to investors. However, in 2022 it decreased, EVA was negative or below 0 (EVA <0). Meanwhile, the calculation using the Market Value Added (MVA) method, the MVA data generated in 2020 is negative where the MVA value is <0. For 2021-2022, it is included in the MVA> 0 category or it can be said that it always produces positive values. It can be concluded that management has been able to increase shareholder wealth.